Las dos paradojas de Alain Wisner. Antropotecnología y ergología - Yves Schwartz (Universidade do Porto, 2012)
Two paradoxes seem to appear throughout Alain Wisner's Anthropotechnology. The first one, from his studies on human labour, leads him to assert that all human beings have equal potentialities, while maintaining at the same time that this universality emerges through history and inheritance which are always specific. The second one leads him to request the cooperation of various areas of human sciences, but without a critical approach, as if they could disregard the consequences of the first paradox.Firstly, it is suggested how it is possible, through the ergological approach, to clear up the first paradox by going deeper into this concept of activity, largely inherited from the wisnerian ergonomy. From an anthropological point of view, it is possible to define live as a universal effort for partly redesigning the frame of local norms which surround human beings and groups.Secondly, the question is : through which crucial scenes the «setting in history» of this universality is developed? Three knots of this « setting in history » are successively considered: body, technical activity and social building of the various spaces where living together proved efficient.In accordance with these points, the basis for a treatment of the second paradox seem yet to be given: if human activity is a permanent crucible for « renormalisations », it constantly reproduces social configurations so that concepts and categories of the human sciences are always partly unprepared in regard to them. Then the question is: how this concept of activity which runs across them all is refracted or taken into account by these sciences? To conclude: if this paper entirely assumes the first paradox, it cannot accept the second one.